2020
DOI: 10.1002/apj.2471
|View full text |Cite
|
Sign up to set email alerts
|

Coal fly ash‐derived mesoporous SBA‐15 as support material for production of liquid hydrocarbon through Fischer–Tropsch route

Abstract: The supernatant solution of silicate species extracted from coal fly ash (CFA) by NaOH fusion is used under acidic conditions with surfactant pluronic P‐123 to prepare the mesoporous silica (SBA‐15). Structural properties of prepared SBA‐15 are found close to those prepared by pure chemicals. Furthermore, the synthesized mesoporous silica (SBA‐15) from CFA is used as support in Fischer–Tropsch synthesis (FTS). The obtained mesoporous material has a surface area of 643 m2/g and a pore size of 8.24 nm. Co–Fe bim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Generally, the preparation of SBA‐15 consists of (a) the formation of micelles in an aqueous solution, (b) the polymerization of an inorganic source, and (c) the removal of surfactants from the pores of the material [49–50] . The SBA‐15 is synthesized by the hydrothermal method in an acidic medium with molar composition: 1.73 TEOS : 0.016 P123 : 18.6 HCl : 133 H 2 O [46,51] . Pluronic triblock copolymer P‐123 [(EO) 20 (PO) 70 (EO) 20 ], a structure‐directing agent, is dissolved in deionized water in an acidic medium with slow addition of TEOS with continuous mechanical stirring.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the preparation of SBA‐15 consists of (a) the formation of micelles in an aqueous solution, (b) the polymerization of an inorganic source, and (c) the removal of surfactants from the pores of the material [49–50] . The SBA‐15 is synthesized by the hydrothermal method in an acidic medium with molar composition: 1.73 TEOS : 0.016 P123 : 18.6 HCl : 133 H 2 O [46,51] . Pluronic triblock copolymer P‐123 [(EO) 20 (PO) 70 (EO) 20 ], a structure‐directing agent, is dissolved in deionized water in an acidic medium with slow addition of TEOS with continuous mechanical stirring.…”
Section: Methodsmentioning
confidence: 99%
“…[49][50] The SBA-15 is synthesized by the hydrothermal method in an acidic medium with molar composition: 1.73 TEOS : 0.016 P123 : 18.6 HCl : 133 H 2 O. [46,51]…”
Section: Preparation Of Sba-15mentioning
confidence: 99%
“…Several types of catalysts are used for the FT process; the most common are Group VIII transition metals i. e., Fe, Co, Ni, and Ru. Ru catalyst favours the hydrogenation of CO and produces long‐chain hydrocarbons [83–84] . Limited reserve and high cost hinder its industrial‐scale application.…”
Section: Fischer‐tropsch Synthesismentioning
confidence: 99%
“…Ru catalyst favours the hydrogenation of CO and produces long-chain hydrocarbons. [83][84] Limited reserve and high cost hinder its industrial-scale application. Nickel also has hydrogenation activity but only favours methane production, also at higher temperatures forms "surface carbonyl" which is volatile and causes the deactivation of the catalyst.…”
Section: Fischer-tropsch Catalystsmentioning
confidence: 99%
“…Several researchers have reported that bimetallic catalysts have immense ability towards production of higher molecular weight hydrocarbons and paraffins during FT synthesis 99–101 . Duvenhage et al .…”
Section: Syngas Productionmentioning
confidence: 99%